FLUID FLOW STUDY IN VARIOUS SHAPES AND SIZES OF HORIZONTAL AXIS SEA CURRENT TURBINE - Wulfilla Maxmilian Rumaherang; Jonny Latuny (SINERGI, 2021)
The ducted tidal turbine models have been developed to utilize the conversion of the kinetic energy on ocean currents. The research in refining the turbine characteristics has been carried out by modifying the turbine’s shape and size. This study investigated flow characteristics in the meridional section of five ducted turbines models for seawater flow with velocity U0 = 1.5 m/s. The ducted turbine design and construction have five different impeller house diameters and fixed inlet and outlet diameters. The potential energy flow theory and experimental data are used to analyze the flow characteristics of the model. The results show that flow velocity in the x-direction at the inlet and outlet cross-section is getting smaller, reducing the impeller house cross section. Each impeller house size reduction increases the flow speed in the impeller house cross-section and also pressure on all other cross-sections tested. In the inlet area, the increased pressure indicates a decrease in speed flow and discharge coefficient value. The discharge coefficient value decreases from CQ = 0.9 at the diameter ratio of dr = 1 to CQ = 0.56 at the diameter ratio of dr = 0.375. The maximum value of power coefficient was determined at dr = 0,61÷0.73 or dr = 0.69 which is equivalent to average internal flow velocity Vr =2.0÷2.6 m/s and the static pressure ps = 97.1÷ 94.4 kPa. At the ratio value of D0/D2 = 0.83, the optimal diameter ratio dropt=0,61÷0.73 is in line with the duct model of case 3 and case 4, but it may be determined solely as for case 4.